2013
DOI: 10.3109/15563650.2013.830733
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the requirement for N-acetylcysteine in paracetamol poisoning from reported dose

Abstract: Context There is contention over whether reported dose correlates with toxicity in paracetamol poisoning and risk assessment is currently based on serum paracetamol concentration compared to a nomogram, irrespective of reported dose.ObjectiveTo determine if reported dose predicts the need for N-acetylcysteine (NAC).MethodsData were taken from paracetamol overdoses presenting to a tertiary toxicology service. Age, sex, reported dose, ingestion time, timed paracetamol concentrations between 4 and 16 h, hepatotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 15 publications
0
21
0
1
Order By: Relevance
“…Recommendations on gastric decontamination have not changed since 2015. Fifty grams of activated charcoal should be administered to a cooperative, awake adult if they present within 2 hours of ingestion of a toxic dose (Box 1) of immediate release paracetamol, or within 4 hours of immediate release paracetamol overdoses greater than 30 g . GRADE: Strong; Evidence: Low .…”
Section: Immediate Release Paracetamol Ingestionmentioning
confidence: 99%
“…Recommendations on gastric decontamination have not changed since 2015. Fifty grams of activated charcoal should be administered to a cooperative, awake adult if they present within 2 hours of ingestion of a toxic dose (Box 1) of immediate release paracetamol, or within 4 hours of immediate release paracetamol overdoses greater than 30 g . GRADE: Strong; Evidence: Low .…”
Section: Immediate Release Paracetamol Ingestionmentioning
confidence: 99%
“…A second limitation of the study was that reported codeine ingestion was not confirmed by laboratory drug analysis, although all paracetamol cases were confirmed by paracetamol concentrations. A previous study using the same database of paracetamol overdoses found a strong association between dose and paracetamol concentration . It has been shown in a number of studies that using patient history is reliable in identifying the drug taken and a good estimate of the drug dose ingested .…”
Section: Discussionmentioning
confidence: 96%
“…12 Some have suggested it might be possible to model acetylcysteine requirements based on estimated paracetamol dose, but this has yet to be tested in practice. 33 …”
Section: Dn Batemanmentioning
confidence: 97%